Facial Genetics: A Brief Overview - Richmond, Stephen; Howe, Laurence J.; Lewis, Sarah; Stergiakouli, Evie; Zhurov, Alexei (Frontiers in Genetics, 2018)
Historically, craniofacial genetic research has understandably focused on identifying the causes of craniofacial anomalies and it has only been within the last 10 years, that there has been a drive to detail the biological basis of normal-range facial variation. This initiative has been facilitated by the availability of low-cost hi-resolution three-dimensional systems which have the ability to capture the facial details of thousands of individuals quickly and accurately. Simultaneous advances in genotyping technology have enabled the exploration of genetic influences on facial phenotypes, both in the present day and across human history. There are several important reasons for exploring the genetics of normal-range variation in facial morphology. • Disentangling the environmental factors and relative parental biological contributions to heritable traits can help to answer the age-old question “why we look the way that we do?” • Understanding the etiology of craniofacial anomalies; e.g. unaffected family members of individuals with non-syndromic cleft lip/palate (nsCL/P) have been shown to differ in terms of normal-range facial variation to the general population suggesting an aetiological link between facial morphology and nsCL/P. • Many factors such as ancestry, sex, eye/hair colour as well as distinctive facial features (such as, shape of the chin, cheeks, eyes, forehead, lips and nose) can be identified or estimated using an individual’s genetic data, with potential applications in healthcare and forensics. • Improved understanding of historical selection and adaptation relating to facial phenotypes, for example, skin pigmentation and geographical latitude. • Highlighting what is known about shared facial traits, medical conditions and genes.